Challenges of the Implementation of the European Charter of Local Self-Government in Polish Legislation (Lex localis - Journal of Local Self-Government, 2018)
Poland is one of the few countries to have ratified the European Charter of Local Self-Government in full and without reservations. The Polish approach is perceived as a positive example of a country’s response to the challenges resulting from recognizing local self-governments as institutions typical of a political system. This article presents the achievements of the Polish legislator in terms of the law of self-government, including a verification of the efficiency of these achievements in view of local self-governance practice. The degree of implementation of the Charter’s provision in the Polish legal system is also outlined. The article covers not only the issues related to a diagnosis of the current state of affairs, but also several specific proposals, guidelines, and suggestions in terms of improving the existing situation.